Minimalisasi Waste Industri Furniture Pada Produksi Rak Botol - Marulan Andivas; Dimaz Harits; Alex Kisanjani (Jurnal Surya Teknika, 2021)
Indonesian furniture products are known to have high competitiveness in the international market. This competitiveness is in the form of unique designs and furniture products with distinctive raw materials such as rattan, bamboo, and teak compared to furniture produced by other countries. PT. XYZ is a company engaged in manufacturing (Furniture). In this study, we will observe the production process of bottle racks ordered by consumers as many as 150 pcs. Based on observations, in the process the company shows that there are activities that do not provide added value resulting in delays in the delivery of ordered products. To find out the cause of the problem, the researcher uses one of the tools from lean manufacturing (Value Stream Mapping) to find waste. Fishbone diagrams in this study were used to help solve the problems found, so that to complete the previous product order which took 44.6 days, it could be completed in 23 days.